A green antibacterial and antiviral coating and preparation method thereof

By combining quercetin with nano copper oxide, antibacterial agents are prepared, and the addition of modified diatomaceous earth and composite fillers, the existing antibacterial and antiviral coatings are solved, and the coatings are realized Excellent antibacterial and antiviral properties and chemical stability.

CN118931266BActive Publication Date: 2025-02-25CHINA KRYPTON NEW ENERGY TECH (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411426594.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing antibacterial and antiviral coatings have problems with poor antibacterial and antiviral effects and poor stability.

Method used

The antibacterial agent is prepared by solution mixing method, and the antibacterial and antiviral properties of the coating are improved by adding modified diatomaceous earth and composite filler.

Benefits of technology

The excellent antibacterial and antiviral properties of the paint are achieved, and the combination of quercetin-modified nano-copper oxide and modified diatomaceous earth improves the chemical stability of the antibacterial agent and extends the antibacterial and antiviral effect of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118931266B_ABST
    Figure CN118931266B_ABST
Patent Text Reader

Abstract

The present invention relates to a green antibacterial and virus-removing coating and a preparation method thereof, and belongs to the technical field of coatings. The raw materials include the following parts by weight: 200-230 parts of styrene-acrylic emulsion, 30-40 parts of composite fillers, 30-40 parts of titanium dioxide, 200-250 parts of deionized water, 3-5 parts of alcohol ester 12, 3-5 parts of dispersant, 2-4 parts of defoamer, 5-10 parts of antibacterial agent, 3-5 parts of wetting agent and 3-6 parts of thickener; the present invention generally uses styrene-acrylic emulsion as a base material, and through the addition of antibacterial agent, composite filler, titanium dioxide, alcohol ester 12 and other additives, the overall performance of the coating is jointly improved. The preparation process of the present invention is simple, green and environmentally friendly, and the prepared coating has excellent antibacterial and antiviral properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to a green antibacterial and antiviral coating and a preparation method thereof. Background Art

[0002] Nowadays, coatings are widely used in various scenes of human life and work, so the importance of antibacterial and antiviral properties of coatings is becoming increasingly prominent. Antibacterial and antiviral coatings can effectively inhibit and kill bacteria and viruses attached to the surface of coatings, reduce the content of microorganisms in indoor air, and thus significantly reduce the risk of disease transmission through contact. This is especially important for crowded places such as homes, schools, and offices, which helps to create a healthier and safer living environment.

[0003] Green paints are often characterized by low volatile organic compound (VOC) emissions, which means they release fewer harmful gases during use, helping to improve indoor air quality and reduce potential threats to human health.

[0004] At present, antibacterial and antiviral coatings are gaining more and more attention, and their market demand is gradually expanding. However, existing antibacterial and antiviral coatings still have problems such as poor antibacterial and antiviral effects and poor stability. Summary of the invention

[0005] The purpose of the present invention is to provide a green antibacterial and antiviral coating and a preparation method thereof. The preparation process of the present invention is simple and green and environmentally friendly, and the prepared coating has excellent antibacterial and antiviral properties.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A green antibacterial and antiviral coating comprises the following raw materials in parts by weight: 200-230 parts of styrene-acrylic emulsion, 30-40 parts of composite filler, 30-40 parts of titanium dioxide, 200-250 parts of deionized water, 3-5 parts of alcohol ester 12, 3-5 parts of dispersant, 2-4 parts of defoamer, 5-10 parts of antibacterial agent, 3-5 parts of wetting agent and 3-6 parts of thickener;

[0008] The preparation process of the antibacterial agent is as follows:

[0009] 5-10 parts of quercetin and 50-65 parts of methanol are mixed at 35-45° C., stirred at 1200-1500 r / min for 30-45 min, then 25-45 parts of nano copper oxide are added, and ultrasonic treatment is performed for 35-60 min. After the treatment, the mixture is filtered, dried at 70-80° C. for 6-10 h, and then ball-milled at a speed of 400 r / min for 3-5 h in a ball mill, and passed through a 200-mesh sieve to obtain the antibacterial agent.

[0010] As a preferred technical solution of the present invention, the preparation process of the composite filler is as follows:

[0011] The diatomite is calcined at 500-600°C for 3-5 hours, cooled to room temperature, and then soaked in an alkaline solution for 1-2 hours, and then rinsed with deionized water and dried to obtain the pretreated diatomite;

[0012] After fully dissolving 20-25 parts of tuckahoe polysaccharide in 70-80 parts of deionized water by weight, 40-50 parts of pretreated diatomaceous earth were added, the system temperature was raised to 60-70°C, stirred for 2-4 hours, and the deionized water was removed by vacuum distillation to prepare modified diatomaceous earth;

[0013] Nano-silicon dioxide, modified diatomaceous earth and anhydrous aluminum silicate are uniformly mixed in a mass ratio of (1-2): (1-2.5): 1, and then ball-milled at a speed of 400 r / min for 3-5 hours in a ball mill, and passed through a 200-mesh sieve to obtain the composite filler.

[0014] As a preferred technical solution of the present invention, the thickener is one or more of sodium carboxyethyl cellulose, hydroxyethyl cellulose ether and hydroxyethyl methyl cellulose.

[0015] As a preferred technical solution of the present invention, the defoaming agent is one or more of polydimethylsiloxane, BYK-358N and BYK-354.

[0016] As a preferred technical solution of the present invention, the dispersant is one of sodium dodecyl sulfate, polyethylene glycol 200 and hexadecyltrimethylammonium chloride.

[0017] As a preferred technical solution of the present invention, the wetting agent is one or more of 4100 wetting agent, GS-2455 silicone wetting agent and BYK3550.

[0018] As a preferred technical solution of the present invention, the alkaline solution is a sodium hydroxide solution with a mass fraction of 15-20%.

[0019] As a preferred technical solution of the present invention, the solid-to-liquid ratio of the diatomaceous earth to the alkaline solution is 1:20 g / mL.

[0020] A method for preparing a green antibacterial and antiviral coating comprises the following preparation steps:

[0021] S1. Prepare an antibacterial agent by mixing the styrene acrylic emulsion and the antibacterial agent in parts by weight, and stir at a speed of 500-700 r / min for 30-40 min to obtain a mixture 1;

[0022] S2, preparing a composite filler, adding the composite filler to the mixture 1, and stirring at 55-65° C. for 15-20 min while maintaining the rotation speed to obtain a mixture 2;

[0023] S3. Continue to add titanium dioxide, deionized water, alcohol ester 12, dispersant, defoamer, wetting agent and thickener, increase the speed to 700-800 r / min and stir for 15-25 min to obtain the green antibacterial and antiviral coating.

[0024] In the present invention, quercetin is dissolved in methanol by a solution mixing method, and then mixed with nano copper oxide particles. By ultrasonic treatment, quercetin molecules can form hydrogen bonds with oxygen atoms on the surface of copper oxide using hydroxyl groups in the structure, so that quercetin can be adsorbed on the surface of nano copper oxide with a large specific surface area, thereby modifying nano copper oxide to prepare an antibacterial agent. Nano copper oxide has excellent antibacterial and antiviral properties, and inhibits bacterial growth and reproduction by destroying bacterial cell membranes, cell structures and functions, and interacts with proteins or nucleic acids on the surface of viruses, thereby destroying viral structures and functions. Nano copper oxide is treated with quercetin. As a natural plant compound, quercetin itself has antibacterial properties. The two are combined by a solution mixing method, and the overall antibacterial effect can be enhanced by synergy. Quercetin exerts antibacterial effects by destroying bacterial cell membranes, inhibiting bacterial enzyme activity or interfering with bacterial metabolism, and copper oxide inhibits bacterial growth by releasing copper ions or generating oxidative stress. The two together improve the overall antibacterial properties of the coating.

[0025] At the same time, since quercetin can modify the surface of nano copper oxide, the chemical stability of nano copper oxide antibacterial agents under different environmental conditions can be enhanced. Copper oxide is prone to oxidative degradation under conditions such as humidity or high temperature, resulting in performance degradation. The modification of quercetin in the present invention can reduce the direct contact between copper oxide and the external environment by modifying the surface of nano copper oxide, thereby delaying its oxidative degradation process and further improving the antibacterial and antiviral properties of the antibacterial agent.

[0026] Poria polysaccharide has shown significant antibacterial properties by improving the ability to remove bacterial biofilms and its own broad-spectrum antibacterial effect. At the same time, Poria polysaccharide has an inhibitory effect on certain viruses and can inhibit the replication process of viruses. Therefore, after being pre-treated with roasting and alkali washing to remove surface impurities and mixing with diatomaceous earth with optimized pores, Poria polysaccharide can be evenly loaded on the surface of diatomaceous earth through the impregnation method. The modified diatomaceous earth further enhances its antibacterial and antiviral effects and provides more comprehensive protection.

[0027] Then, the composite filler is prepared by ball milling with nano-silicon dioxide and anhydrous aluminum silicate. Anhydrous aluminum silicate can increase the viscosity and fluid properties of the coating, improve the dispersion and coating properties of the coating, and make the coating more uniform and smooth. Therefore, it can effectively isolate bacteria and viruses from direct contact with the coating substrate, thereby reducing the chances of microorganisms adhering to and reproducing on the coating surface. In addition, anhydrous aluminum silicate has good chemical stability and is not easily decomposed or eroded by microorganisms. Its application in coatings can help improve the chemical stability of the coating, which helps to keep the coating surface smooth, clean and antibacterial, and prolong the antibacterial and antiviral effects of the coating.

[0028] At the same time, adding alcohol ester 12 as a film-forming aid to the coating can significantly improve the film-forming properties of the coating, forming a denser and smoother film layer on the coating surface. This film layer is conducive to blocking the invasion of bacteria and viruses, thereby improving the antibacterial and antiviral properties of the coating. In addition, alcohol ester 12 has good chemical stability and hydrolysis stability, which can ensure that the coating maintains stable performance during storage and use, thereby ensuring the durability of the antibacterial and antiviral effect.

[0029] Titanium dioxide is added to the paint, which has excellent photocatalytic properties. Under light conditions, the generated free radicals with strong oxidizing properties can effectively destroy the cell structure of bacteria and viruses, thereby achieving antibacterial and antiviral effects. In antibacterial and antiviral paints, the addition of titanium dioxide helps to form a uniform and dense coating film, further enhancing the antibacterial and antiviral barrier of the paint.

[0030] Beneficial effects of the present invention:

[0031] The invention improves the antibacterial and antiviral properties of the antibacterial agent by modifying nano copper oxide with quercetin, and further increases the overall antibacterial property of the coating by using a composite filler obtained by ball-milling diatomaceous earth, nano silicon dioxide and anhydrous aluminum silicate modified with tuckahoe polysaccharide. Styrene acrylic emulsion is used as a matrix material, and titanium dioxide, alcohol ester 12 and other additives are added to jointly improve the overall performance of the coating, which has excellent antibacterial and antiviral properties. The invention also has a simple preparation process and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0033] Figure 1 This is a SEM electron microscope image of the antibacterial agent prepared in Example 1;

[0034] Figure 2 This is the TEM electron microscope image of the modified diatomite prepared in Example 1. DETAILED DESCRIPTION

[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0036] In the following examples and comparative examples:

[0037] Quercetin: purchased from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.;

[0038] Nano copper oxide: purchased from Shanghai Kelaman Reagent Co., Ltd.

[0039] Styrene acrylic emulsion: purchased from Wuhan Jiyesheng Chemical Co., Ltd., product number A00093;

[0040] Diatomaceous earth: purchased from Jinan Liyang Chemical Co., Ltd.

[0041] Poria polysaccharide: purchased from Shanxi Yuning Biotechnology Co., Ltd.

[0042] Nano-silicon dioxide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: S817567;

[0043] Anhydrous aluminum silicate: purchased from Wuhan Jiyesheng Chemical Co., Ltd., product number: A00209;

[0044] Titanium dioxide: purchased from Hubei Chengfeng Chemical Co., Ltd.

[0045] Alcohol ester 12: purchased from Hubei Chengfeng Chemical Co., Ltd.;

[0046] Sodium dodecyl sulfate: purchased from Shandong Tongfengqi Chemical Co., Ltd., product number: 55B;

[0047] 4100 wetting agent: purchased from Guangdong Deqian New Materials Co., Ltd.;

[0048] BYK-354: purchased from Shanghai Huasen Chemical Co., Ltd.;

[0049] Sodium carboxyethyl cellulose: purchased from Shanghai Lumeng Technology Co., Ltd.

[0050] Example 1

[0051] S1. Preparation of antimicrobial agent:

[0052] At 35° C., 5 parts of quercetin and 50 parts of methanol were mixed, stirred at 1200 r / min for 30 min, then 25 parts of nano copper oxide were added, and ultrasonic treatment was performed for 35 min. After the end, the mixture was filtered, dried at 70° C. for 6 h, and then ball-milled at a speed of 400 r / min for 3 h in a ball mill, and passed through a 200-mesh sieve to obtain the antibacterial agent;

[0053] According to weight proportions, 200 parts of styrene acrylic emulsion and 5 parts of antibacterial agent were mixed, and stirred at a speed of 500 r / min for 30 min to obtain a mixture 1.

[0054] S2. Preparation of composite filler:

[0055] The diatomite was calcined at 500°C for 3 hours, cooled to room temperature, and then immersed in an alkaline solution for 1 hour, and then rinsed with deionized water and dried to obtain the pretreated diatomite;

[0056] By weight, 20 parts of tuckahoe polysaccharide were fully dissolved in 70 parts of deionized water, and then 40 parts of pretreated diatomaceous earth were added, the system temperature was raised to 60° C., stirred for 2 hours, and the deionized water was removed by reduced pressure distillation to prepare modified diatomaceous earth;

[0057] After uniformly mixing nano-silicon dioxide, modified diatomaceous earth and anhydrous aluminum silicate in a mass ratio of 1:1:1, the mixture was ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the composite filler;

[0058] 30 parts of composite filler were added to mixture 1, and stirring was continued at 55° C. for 15 minutes while maintaining the rotation speed to obtain mixture 2.

[0059] S3. Continue to add 30 parts of titanium dioxide, 200 parts of deionized water, 3 parts of alcohol ester 12, 3 parts of sodium dodecyl sulfate, 2 parts of BYK-354, 3 parts of 4100 wetting agent and 3 parts of sodium carboxyethyl cellulose, increase the speed to 700r / min and stir for 15 minutes to obtain the green antibacterial and antiviral coating.

[0060] Figure 1 This is the SEM electron microscope image of the antibacterial agent prepared in Example 1, and it can be seen that the surface structure of copper oxide has changed; Figure 2 This is a TEM electron microscope image of the modified diatomite prepared in Example 1. The structural state of the modified diatomite can be seen from the electron microscope image.

[0061] Example 2

[0062] S1. Preparation of antimicrobial agent:

[0063] At 40° C., 8 parts of quercetin and 55 parts of methanol were mixed, stirred at 1300 r / min for 38 minutes, then 35 parts of nano copper oxide were added, and ultrasonic treatment was performed for 50 minutes. After the end, it was filtered, dried at 75° C. for 6-10 hours, and then ball-milled at a speed of 400 r / min for 4 hours in a ball mill, and passed through a 200-mesh sieve to obtain the antibacterial agent;

[0064] According to weight proportions, 210 parts of styrene acrylic emulsion and 8 parts of antibacterial agent were mixed, and stirred at a speed of 600 r / min for 35 min to obtain a mixture 1.

[0065] S2. Preparation of composite filler:

[0066] The diatomite was calcined at 550°C for 4 hours, cooled to room temperature, and then soaked in an alkaline solution for 1.5 hours, then rinsed with deionized water and dried to obtain the pretreated diatomite;

[0067] After fully dissolving 23 parts of Poria cocos polysaccharide in 75 parts of deionized water, 45 parts of pretreated diatomaceous earth were added, the system temperature was raised to 65° C., stirred for 3 hours, and the deionized water was removed by reduced pressure distillation to prepare modified diatomaceous earth;

[0068] After uniformly mixing nano-silicon dioxide, modified diatomaceous earth and anhydrous aluminum silicate in a mass ratio of 1.5:2:1, the mixture was ball-milled at a speed of 400 r / min for 4 hours, and passed through a 200-mesh sieve to obtain the composite filler;

[0069] 35 parts of composite filler were added to mixture 1, and stirring was continued at 60° C. for 18 minutes while maintaining the rotation speed to obtain mixture 2.

[0070] S3. Continue to add 35 parts of titanium dioxide, 220 parts of deionized water, 4 parts of alcohol ester 12, 4 parts of sodium dodecyl sulfate, 3 parts of BYK-354, 4 parts of 4100 wetting agent and 5 parts of sodium carboxyethyl cellulose, increase the speed to 750r / min and stir for 20 minutes to obtain the green antibacterial and antiviral coating.

[0071] Example 3

[0072] S1. Preparation of antimicrobial agent:

[0073] 10 parts of quercetin and 65 parts of methanol were mixed at 45°C, stirred at 1500 r / min for 45 minutes, then 45 parts of nano copper oxide were added, and ultrasonic treatment was performed for 60 minutes. After the end, it was filtered, dried at 80°C for 10 hours, and then ball-milled at a speed of 400 r / min for 5 hours by a ball mill, and passed through a 200-mesh sieve to obtain the antibacterial agent;

[0074] According to weight proportions, 230 parts of styrene acrylic emulsion and 10 parts of antibacterial agent were mixed, and stirred at a speed of 700 r / min for 40 min to obtain a mixture 1.

[0075] S2. Preparation of composite filler:

[0076] The diatomite was calcined at 600°C for 5 hours, cooled to room temperature, and then immersed in an alkaline solution for 2 hours, and then rinsed with deionized water and dried to obtain the pretreated diatomite;

[0077] By weight, 25 parts of tuckahoe polysaccharide were fully dissolved in 80 parts of deionized water, and then 50 parts of pretreated diatomaceous earth were added, the system temperature was raised to 70°C, stirred for 4 hours, and the deionized water was removed by reduced pressure distillation to prepare modified diatomaceous earth;

[0078] After uniformly mixing nano-silicon dioxide, modified diatomaceous earth and anhydrous aluminum silicate in a mass ratio of 2:2.5:1, the mixture was ball-milled at a speed of 400 r / min for 5 hours, and passed through a 200-mesh sieve to obtain the composite filler;

[0079] 40 parts of the composite filler were added to the mixture 1, and the mixture was stirred at 65° C. for 20 minutes while maintaining the rotation speed to obtain the mixture 2.

[0080] S3, continue to add 40 parts of titanium dioxide, 250 parts of deionized water, 5 parts of alcohol ester 12, 5 parts of sodium dodecyl sulfate, 4 parts of BYK-354, 5 parts of 4100 wetting agent and 6 parts of sodium carboxyethyl cellulose, increase the speed to 800r / min and stir for 25 minutes to obtain the green antibacterial and antiviral coating.

[0081] Comparative Example 1

[0082] The difference between Comparative Example 1 and Example 1 is that the nano copper oxide in Comparative Example 1 is not modified by quercetin, and the other operations are the same.

[0083] Comparative Example 2

[0084] The difference between Comparative Example 2 and Example 1 is that the diatomaceous earth in Comparative Example 2 is not modified by pachymaran, and the other operations are the same.

[0085] Comparative Example 3

[0086] The difference between Comparative Example 3 and Example 1 is that diatomaceous earth is not added to the composite filler in Comparative Example 3, and the other operations are the same.

[0087] Performance Test:

[0088] 1. Antibacterial property:

[0089] Test method: According to HG / T 3950-2007 Antimicrobial Coatings: Appendix A Antimicrobial Coatings - Antibacterial Performance Test Method, taking Escherichia coli (AS1.90) and Staphylococcus aureus (AS1.89) as examples, the inoculation concentration is 7.2 cfu / mL;

[0090] 2. Antiviral activity:

[0091] Test method: ISO 21702:2019, using influenza A virus H1N1 (A / PR / 8 / 34) as the test virus and MDCK cells as the host for testing. The test results are shown in Table 1:

[0092] Table 1

[0093]

[0094] According to the above data, the antibacterial property of the coatings prepared in the examples reaches 99.99%, and the antiviral property is greater than 99%. The data of the examples are better than those of the comparative examples, indicating that the coatings prepared by the method of the present invention have excellent antibacterial and antiviral properties.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A green antibacterial and antiviral coating, characterized in that: The invention comprises the following raw materials in parts by weight: 200-230 parts of styrene-acrylic emulsion, 30-40 parts of composite filler, 30-40 parts of titanium dioxide, 200-250 parts of deionized water, 3-5 parts of alcohol ester 12, 3-5 parts of dispersant, 2-4 parts of defoamer, 5-10 parts of antibacterial agent, 3-5 parts of wetting agent and 3-6 parts of thickener; The preparation process of the antibacterial agent is as follows: 5-10 parts of quercetin and 50-65 parts of methanol are mixed at 35-45° C., stirred at 1200-1500 r / min for 30-45 min, then 25-45 parts of nano copper oxide are added, and ultrasonic treatment is performed for 35-60 min. After the end, the mixture is filtered, dried at 70-80° C. for 6-10 h, and then ball-milled at a speed of 400 r / min for 3-5 h in a ball mill, and passed through a 200-mesh sieve to obtain the antibacterial agent; The preparation process of the composite filler is as follows: The diatomite is calcined at 500-600°C for 3-5 hours, cooled to room temperature, and then soaked in an alkaline solution for 1-2 hours, and then rinsed with deionized water and dried to obtain the pretreated diatomite; After fully dissolving 20-25 parts of tuckahoe polysaccharide in 70-80 parts of deionized water by weight, 40-50 parts of pretreated diatomaceous earth were added, the system temperature was raised to 60-70°C, stirred for 2-4 hours, and the deionized water was removed by vacuum distillation to prepare modified diatomaceous earth; The nano-silicon dioxide, modified diatomaceous earth and anhydrous aluminum silicate are uniformly mixed in a mass ratio of (1-2): (1-2.5): 1, and then ball-milled at a speed of 400 r / min for 3-5 hours in a ball mill, and passed through a 200-mesh sieve to obtain the composite filler; The preparation method of the green antibacterial and antiviral coating comprises the following preparation steps: S1. Prepare an antibacterial agent. Mix the styrene acrylic emulsion and the antibacterial agent by weight, and stir at a speed of 500-700 r / min for 30-40 min to obtain a mixture 1; S2, preparing a composite filler, adding the composite filler to the mixture 1, and stirring at 55-65° C. for 15-20 min while maintaining the rotation speed to obtain a mixture 2; S3. Continue to add titanium dioxide, deionized water, alcohol ester 12, dispersant, defoamer, wetting agent and thickener, increase the speed to 700-800 r / min and stir for 15-25 min to obtain the green antibacterial and antiviral coating.

2. The green antibacterial and antiviral coating according to claim 1, characterized in that: The thickener is one or more of sodium carboxyethyl cellulose, hydroxyethyl cellulose ether and hydroxyethyl methyl cellulose.

3. The green antibacterial and antiviral coating according to claim 1, characterized in that: The defoaming agent is one or more of polydimethylsiloxane, BYK-358N and BYK-354.

4. The green antibacterial and antiviral coating according to claim 1, characterized in that: The dispersant is one of sodium lauryl sulfate, polyethylene glycol 200 and hexadecyltrimethylammonium chloride.

5. The green antibacterial and antiviral coating according to claim 1, characterized in that: The wetting agent is one or more of 4100 wetting agent, GS-2455 silicone wetting agent and BYK3550.

6. The green antibacterial and antiviral coating according to claim 1, characterized in that: The alkaline solution is a sodium hydroxide solution with a mass fraction of 15-20%.

7. The green antibacterial and antiviral coating according to claim 1, characterized in that: The solid-to-liquid ratio of the diatomaceous earth to the alkaline solution is 1:20 g / mL.

Citation Information

Patent Citations

  • Packaging container with antibacterial and antiseptic effects and manufacturing method thereof

    CN115674790A

  • Efficient mildew-proof sterilizing fireproof interior wall paint and preparation method thereof

    CN118421139A